2019
DOI: 10.1021/acsami.9b14329
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed ZnxCd1–xS Buffer Layers for Vapor Transport-Deposited SnS Thin-Film Solar Cells: Achieving High Open-Circuit Voltage

Abstract: As an alternative buffer material to CdS, Zn x Cd1–x S buffer layers for vapor transport-deposited SnS thin-film solar cells (TFSCs) were fabricated using the successive ionic layer adsorption and reaction (SILAR) method. Varying the Zn-to-Cd ratio resulted in a series of Zn x Cd1–x S thin films with controllable band gaps in the range of 2.40–3.65 eV. The influence of the Zn-to-Cd ratio on the cell performance was investigated in detail. The Zn0.34Cd0.66S buffer layer was found to be the optimal composition f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…In addition, Table 2 shows the detailed photovoltaic characteristics of the SnS solar cells, i.e., series resistance (R S ), shunt resistance (R Sh ), ideality factor of a diode (n), and the reverse saturation current (J 0 ), which were obtained from the J-V relationship of the single-junction solar cells (Section S2, Supporting Information), [29] together with the thickness of SnS layer (d). As shown in Table 2, the V OC of the homojunction solar cells fabricated in this study was remarkably high after the heterojunction solar cells fabricated by Pawar et al in 2020 ((V OC ¼ 405 mV with η ¼ 3.72%), [16] The properties of undoped SnS thin film are those of the film deposited on the SiO 2 glass substrate under the same conditions as the films deposited on the n-type SnS single crystals; b) The study by Kawanishi et al [22] Chua et al in 2019 ((V OC ¼ 400 mV with η ¼ 2.21%), [15] and Sinsermsuksakul et al in 2014 ((V OC ¼ 372 mV with η ¼ 4.4%). [13] To investigate the built-in potential (V bi ), acceptor and donor concentrations (N A and N D , respectively), and the depletion region of the n-type and p-type layers (w n and w p , respectively), the capacitance-reverse bias voltage (C-V ) characteristics were analyzed using Equation ( 1) and ( 2)…”
Section: Photovoltaic Properties Of Sns Homojunction Solar Cellmentioning
confidence: 53%
See 2 more Smart Citations
“…In addition, Table 2 shows the detailed photovoltaic characteristics of the SnS solar cells, i.e., series resistance (R S ), shunt resistance (R Sh ), ideality factor of a diode (n), and the reverse saturation current (J 0 ), which were obtained from the J-V relationship of the single-junction solar cells (Section S2, Supporting Information), [29] together with the thickness of SnS layer (d). As shown in Table 2, the V OC of the homojunction solar cells fabricated in this study was remarkably high after the heterojunction solar cells fabricated by Pawar et al in 2020 ((V OC ¼ 405 mV with η ¼ 3.72%), [16] The properties of undoped SnS thin film are those of the film deposited on the SiO 2 glass substrate under the same conditions as the films deposited on the n-type SnS single crystals; b) The study by Kawanishi et al [22] Chua et al in 2019 ((V OC ¼ 400 mV with η ¼ 2.21%), [15] and Sinsermsuksakul et al in 2014 ((V OC ¼ 372 mV with η ¼ 4.4%). [13] To investigate the built-in potential (V bi ), acceptor and donor concentrations (N A and N D , respectively), and the depletion region of the n-type and p-type layers (w n and w p , respectively), the capacitance-reverse bias voltage (C-V ) characteristics were analyzed using Equation ( 1) and ( 2)…”
Section: Photovoltaic Properties Of Sns Homojunction Solar Cellmentioning
confidence: 53%
“…However, despite significant efforts to improve the V OC , the highest V OC is still limited to ≈400 mV, resulting in conversion efficiency ( η) of 2−4%. [ 15,16 ] A recent study reported a η of 4.8% with a V OC of 330 mV for a p‐SnS/n‐TiO 2 heterojunction, [ 17 ] which is the highest reported value for any SnS‐containing solar cells; however, this value is much lower than the theoretical value of SnS homojunction solar cell ( η = 25% at a V OC of 985 mV). [ 18 ] This implies that a further increase in the V OC of SnS heterojunction solar cell is considerably difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, SnS/2D nanomaterial hybrids in a sandwiched model were also intensively investigated for targeted applications, such as high-performance solar cells, [133][134][135][136] and electronic devices. [137][138][139][140] For instance, in 2018, the facile morphology control of anisotropic SnS was realized via regulated growth kinetics during vapor transport deposition (VTD), and SnS/2D CdS heterostructure-based thin film solar cells were fabricated to study the impact of the SnS morphology.…”
Section: Sandwiched Modelmentioning
confidence: 99%
“…Recently, some studies have shown that doping of SnS with aluminum (Al), iron (Fe), indium (In), copper (Cu) and silver (Ag) can enhance its photovoltaic properties [8][9][10][11][12]. Doped and undoped SnS lms can be deposited by several techniques such as RF magnetron sputtering [8], vapor transport deposition (VTD) [13], e-beam evaporation [14], thermal evaporation [15], electrodeposition [10], chemical bath depositions [7], spray pyrolysis [12]. However, very few studies that investigate the effect of Cu doping on the physical properties of large cubic phase of SnS by spray pyrolysis exist in the literature.…”
Section: Introductionmentioning
confidence: 99%